Cherry-Picked Intelligence. The Weapons of Mass Destruction Dispositiv e as a Legitimation for National Security in the Post 9/11 Age - Heide, Liesbeth (Historical Social Research / Historische Sozialforschung, 2013)
»Geheimdienste mit Scheuklappen: Das Dispositiv der Massenvernich tungswaffen als Legitimation für Nationale Sicherheit nach 9/11&# xab;. The claim that Iraq possessed Weapons of Mass Destruction (WMD) led to the invasion of Iraq in 2003 by the US army. For the George W. Bush administration, the likely presence of WMD in Iraq was the major justification for going to war. However, Bush' opponents suspected he used the WMD-dispositive as a legitimation for an invasion that was al ready set in motion for different reasons. The Iraq invasion and the u nderlying ideas about the presence of WMD thus provide a tangible case for the analysis of theories of conspiracy and security. The developm ent of the WMD-dispositive will be contextualized using the toolkit of securitization theory. The article explores the notions of security a nd conspiracy that were used to build the dispositive and shows how it ultimately failed and turned into a counter-narrative in which the Bu sh administration itself became the Great Conspirator.